Exploring The Factors on Student Satisfaction with Digital Payments in Higher Education - Saksono, Lalang (Jurnal Pendidikan Humaniora, 2023)
The aim of this research is to analyze the factors influencing student satisfaction with the use of digital payment in higher education institutions in Central Java. The research method employed is quantitative, utilizing linear regression analysis. The research findings indicate that the perceived usefulness has a positive and significant impact on student satisfaction regarding the use of digital payment using the Technology Acceptance Model approach in several higher education institutions in Central Java. Perceived ease of use, on the other hand, does not have a significant impact on student satisfaction with the use of digital payment using the Technology Acceptance Model approach in higher education institutions in Central Java. Perceived trust also has a positive and significant influence on student satisfaction with the use of digital payment using the Technology Acceptance Model approach among students in higher education institutions in Central Java. However, perceived security and risk do not have a significant impact on student satisfaction with the use of digital payment using the Technology Acceptance Model approach among students in higher education institutions in Central Java. It is important to note that factors such as perceived usefulness, perceived ease of use, perceived trust, and perceived security and risk collectively have an impact on student satisfaction when using digital payment.